The effect of current ratio (CR), debt equity ratio (DER), and net profit margin (NPM) on stock price - Fransiska Simanullang; Sairun Simanullang (Priviet Social Sciences Journal, 2022)
During this pandemic there are many traders (people who invest in the short term or more actively monitor market prices), and retail investors (people who invest in the long term with small capital or passively monitor market prices and buy commodities). regularly either per day, week, or month with a small capital). This study uses the annual financial reports of three different infrastructure sector companies, namely, PT Jasa Marga Tbk, PT Waskita Karya (Persero) Tbk, and PT Bali Tower Indo Sentra Tbk and the data is taken from the Indonesia Stock Exchange on the website www.idx. co.id with the aim of obtaining empirical evidence that can be tested using the causality method. Data analysis in this study was carried out using multiple linear regression. This test begins with descriptive statistical testing, then continues with classical assumption testing and ends with hypothesis testing. The program (software) used for data processing in this study is SPSS version 22. The results of the study partially prove that the Debt to Equity Ratio (DER) has a significant effect on stock prices in Infrastructure sector companies for the 2016-2020 period. The results of the study partially prove that Net Profit Margin (NPM) has no significant effect on stock prices in Infrastructure sector companies for the 2016-2020 period. The results simultaneously prove that the Debt to Equity Ratio (DER) and Net Profit Margin (NPM) have a significant effect on stock prices in Infrastructure sector companies for the 2016-2020 period.